The Upper Devonian palynostratigraphy and organic matter maturation of the Pulo do Lobo Domain, South Portuguese Zone, Portugal - Pereira, Zélia (2014)
Palynostratigraphic research in the Pulo do Lobo Domain, South Portuguese Zone, Iberian Variscides, allows the age revision and the following correlations among the composing stratigraphic units: the Pulo do Lobo and Atalaia Formations exhibit lithological and deformational affinities, and no age determination was achieved; the Ribeira de Limas and Gafo formations are of early Frasnian and the Santa Iria, Horta da Torre and Represa formations. yielded palynomorphs oflate Famennian age. Vitrinite reflectance values of the organic matter indicate that the Pulo do Lobo and Atalaia formations reach the higher greenschist facies of metamorphism while all the overlying units belong to the upper epizone. The metamorphic and structural contrasts suggest that the Pulo do Lobo!Atalaia formations were once part of a pre-Famennian accretionary prism related to a northward subduction while all the other overlying units were laid down in a sedimentary basin, discordant over that paleoprism. From all these data, it is inferred that this basin and the Iberian Pyrite Belt basin were part of the same paleogeographic realm during the late Devonian.